ICTforAg 2023: Cultivating inclusion - Koo, Jawoo; Goss, Courtney (International Food Policy Research Institute, 2023)
ICTforAg is an annual convening where agricultural stakeholders and technology experts come together to share knowledge, find solutions, and form partnerships to address challenges in agri-food systems across low- and middle-income countries. The main goal of ICTforAg is to grow communities and catalyze meaningful conversations, insights, and collaborations, increase participation of participants from the developing world, promote knowledge sharing and learning, and inspire practitioners to develop inclusive and sustainable ICT solutions. ICTforAg has a strong history since 2015 and owes its success to the contributions made by various organizations to build this community. In 2023, CGIAR and DevGlobal, in partnership with USAID Feed the Future and DAI Digital Frontiers, jointly implemented ICTforAg 2023 as a global online conference on November 7-9 with 145 speakers across 40 sessions. Out of the 2,608 individuals who registered for the event, a total of 1,778 attendees (constituting 68% of registrants) participated over the three days. In addition to the main sessions, the conference also featured the Expo, virtual exhibition space that allowed various organizations from academia, research, and the private sector to showcase their innovations interactively, the Inspire Challenge, a new Pay-for-Results program intended to increase women’s participation in digital agri-food advisory services and programs, the ICTforAg+ Satellite Events, a series of locally-led satellite events in four countries (Indonesia, Mexico, Nepal, and India), and the ICTforAg Learning Network, an online platform designed to support the collaboration amongst the global ICTforAg community of practice.